Avaliação das ações do Programa Mulher, Viver Sem Violência, no âmbito da Casa da Mulher Brasileira, em Fortaleza- Ceará - Mesquita, Irlanda Brandão (2022)
In Brazil, in 2013, against the Dilma Rousseff administration was implemented the Public Policy intituled Programa Mulher, Viver sem Violência, and created the "Casa da Mulher Brasileira-CMB"; one of the objectives was to find a means of working on the issue of violence against women. The institution outlines social facilities that bring together several integrated services for protection and to guarantee their rights. In 2018 was installed the first institution in Ceara, which aims to combat violence against women. This research seeks to assess if the activities carried out in the CMB-CE have corresponded to the precepts of the Programa Mulher, Viver sem Violência, and, consequently, the purpose of the National Policy to combat violence against women. For that, examined the implementation, the alignments, the national and local formulation contexts, the normative aspects, and the perception of the involved subjects related to the object of study. The research was qualitative and elaborated under the In-Depth Assessment panorama and your four axes: political, economic, and social contexts.This research bibliographic used a feminist collective composed of classic international writers and Brazilian authors such as Flávia Biroli, Lourdes Maria Bandeira, Suely Souza de Almeida, and others. Interviewed the institution workers and held focus groups with women users of the Policy from the field research. Data Analysis was based on Analysis of Discourse by Eni Orlandi (2005), extracting the categories and subcategories raised in the field. The results showed that public policies such as the CMB help to understand the cycle of violence against women, identifying the reasons for such a significant increase in cases of gender violence. Observed from the collected indicators that the institution is frequently required by Ceara women, which proves to be an effective instrument for a series of consults in the same place. According to survey data on the social participation of CMB-CE, professionals, and users of the social policy; through interviews and focus groups, observed social and human changes in women, professionals, and users of the policy. Ceara Institutions. Brazil has made progress by adopting a program to combat violence against women and Ceara Institutions stands out in the country for ensuring the existence of the CMB in the Capital - Fortaleza, expanding to the rest of the State.